AKTIVITAS MUKOLITIK EKSTRAK DAUN ILER (Coleus atropurpureus [L.] benth.) SECARA IN VITRO - Sulastri Herdaningsih; Dian Kartikasari (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
Cough is a protective physiological mechanism to stimulate and cleanse the respiratory system of foreign objects that can cause infection. Traditional cough treatment is preferred because of the relatively low side ffects compared tochemical drugs. In some areas, Iler leaves are used as cough medicine. The purpose of this study was to determine the mucolytic activity of ethanol extract of Iler leaves on duck egg white which was added to the test solution every 15 minutes, namely at minutes 0,15,30,45, and 60. Viscosity measurements were carried out in the positive control group, negative control group, 3% group, 4,5% group and 6% group. The results obtained showed that Iler leaves extract was able to significantly reduce the viscosity of duck egg whites compare to the negative control. The ethanol extract of Iler leaves has mucolytic activity against duct egg white in vitro at a concetnration range of 3-6%.